Quest for the Origins of the First Americans, by E. James Dixon (1993). University of New Mexico Press - Bostwick, Todd W. (Bulletin of the History of Archaeology, 1994)
In recent years, Paleoindian research has seen numerous advances in data, approaches and ideas. With each new book or article, a better understanding of the origins of the first Americans is gained. Yet, heated debate on the' subject continues, and as researchers scrutinize new data, old approaches and models are re-evaluated. The history of Paleoindian research and the methodology of archaeological inquiry often are a part of the debate. Dixon's book is a welcome addition to this debate.The three major themes of Dixon's book are outlined in the book',s preface. The first theme is the documentation, synthesis, and interpretation of the early prehistory of the Western North American Arctic and Subarctic regions. The second theme is the process of scientific inquiry including the excitement of research and the social context of intellectual growth. This second theme has two components: (1) following ,established procedures of a discipline, and (2) the use of innovative new methods or discoveries. The third theme is the history of archaeology of Alaska. Dixon also notes in the preface that the book is directed to a broad and diverse audience, not just other archaeologists. This later comment is evident in Dixon's clear, relatively jargon free writing style. Although the book cover notes state that the book was written for a lay audience, there is much in the book that professional archaeologists as well can gain by reading the book.